Changes in breeding soundness evaluation during a breeding season - Thompson, A.W.; Marston, T.T.; Sanderson, M.; Chenoweth, P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Breeding-soundness evaluations are a common tool in the beef industry to test a bull’s potential fertility. These evaluations place a bull into one of three categories: satisfactory, unsatisfactory, or deferred. These categories only refer to the bull at a specific time, and his status can and will change over time. The purpose of this report is to explain and demonstrate the changes in a bull’s breeding- soundness evaluations during a breeding season.
Keywords: Beef; Breeding; Soundness